Digital Servitization Influencing SME Performance - Pitawong, Panisara; Ueasangkomsate, Pittawat (Journal of Social Sciences and Humanities Research in Asia, 2025)
This aim of this research is to study the factors of digital servitization which influence the performance of small and medium-sized enterprises (SMEs) in the restaurant service business sector, specifically analyzing impact to performance. The factors of digital servitization include identity, dematerialization, and collaboration. The business performance includes financial perspective, customer perspective, internal process perspective and learning and growth perspective. The sample population of this study is 381 medium and small restaurant service businesses in Bangkok and the surrounding area. Convenient sampling was used due to the time constraints and lack of access to restaurant businesses that were ready to provide information during the study period. A questionnaire was used to collect data and the data was analyzed by using statistics of mean, standard deviation, percentage, and multiple linear regression analysis. The findings found that the use of digital servitization in terms of dematerialization and collaboration have a statistically significant influence on the business performance for both financial and customer perspectives at a level of 0.05. The factors of using digital servitization in terms of identity and collaboration perspectives have a statistically significant influence on the business performance of internal processes and learning and growth perspectives at a statistical level of 0.05. Consequently, the research findings indicate that SMEs should focus on the implementation of digital servitization concepts in their operations, emphasize providing more services to customers. This results in reducing unnecessary costs and increases the value of the restaurants performance. These factors also affect the overall business performance to be more efficient in the future.